Investigation and evaluation of main indicators impacting synchromodality using ARTIW and AHP methods - Šakalys, Raimondas; Sivilevičius, Henrikas; Miliauskaitė, Laima; Šakalys, Algirdas (Transport, 2019)
The East-West Transport Corridor (EWTC) in the Southern part of the Baltic Sea Region (BSR) has been chosen as a practical area for implementation of a novel transportation concept called synchromodality. The main expectations in developing synchromodal transport system are related to the improvement of the transport service level, modal shift and capacities utilization of transport hubs along this corridor. However, in the absence of identification of major factors influencing synchromodal system it is difficult to evaluate a potential benefit of implementation of this new transport concept. Our main goal in this paper was, on the basis of a review and using a specific questionnaire, to determine the main indicators impacting effectiveness of the synchromodal system. Compatibility of experts’ opinions was verified by using Multiple-Criteria Decision-Making (MCDM) method. The paper will be useful for transport and logistics companies interested in moving towards synchromodal transport, as well as for future researchers. In the course of the research – using the Average Rank Transformation Into Weight (ARTIW) and Analytic Hierarchy Process (AHP) methods – it was determined that the normalized subjective weights of the five main criteria impacting synchromodality distributed in the following order: service quality, efficiency, infrastructure sufficiency, technical properties of terminals and interaction of technologies. In accordance with the Kendall’s concordance coefficient and consistency ratio values, expert opinions are consistent, which enabled the rankings of expert group averages and the eigenvector to take as a result of the task solution. The outcomes of the research presented in the paper have shown that service quality (transport time, service and waiting time, handling time, working hours, reliability and flexibility) is the most important indicator (criterion) impacting synchromodality. At the same time it is a big challenge for transport researchers because it requires to design and apply a qualitatively new mathematical models facilitating an establishment of an optimal synchromodal network and services along chosen transport corridor.